Волновые процессы в ионосфере над Европой, сопровождавшие солнечное затмение 20 марта 2015 г. - Черногор, Л.Ф. (Кинематика и физика небесных тел, 2016)
По данным сети ионозондов, расположенных в Европе, проанализированы ионосферные возмущения на высоте около 300 км, которые сопутствовали солнечному затмению 20 марта 2015 г. Подтверждено, что затмение сопровождалось генерацией гравитационных волн в нейтральной атмосфере и перемещающихся ионосферных возмущений. Период последних был 30...100 мин, а амплитуда относительных возмущений концентрации электронов составляла 4...19 %. Возмущения продолжались не менее 2 ч. В течение затмения амплитуда возмущений чаще увеличивалась, в одном случае она уменьшалась в результате подавления наблюдавшегося прежде волнового процесса процессом, сгенерированным затмением. За даними мережі іонозондів, розташованих у Європі, проаналізовано іоносферні збурення на ви-соті 300 км, що супроводжували сонячне затемнення 20 березня 2015 р. Підтверджено, що затемнення супроводжувалось генерацією гравітаційних хвиль у нейтральній атмосфері та рухомих іоносферних збурень. Період останніх дорінював 30...100 хв, а амплітуда відносних збурень концентрації електронів складала 4...19 %. Збурення продовжувалися не менше ніж 2 год. Протягом затемнення амплітуда збурень частіше збільшувалась, в одному випадку вона зменшувалась у результаті придушення хвильового процесу, який спостерігався раніше, процесом, що був згенерований затемненням. To identification of temporal variations of the characteristics of the Jupiter’s cloud layer we take into account the rotation of the planet caused by geometrical modulation, and its orbital motions. Inclination of the axis of rotation to the orbital plane of Jupiter is 3.13°, the angle between the magnetic axis and the axis of rotation β ≈ 10°. Therefore, during the Jovian year Jovicentric magnetic declination of the Earth jm varies from –13.13 to +13.13° and under-the-Sun point on Jupiter’s magnetosphere is changed to 26.26° per orbital period. In this connection variation of Jovimagnetic latitude of the Earth on Jupiter will be a preferably on the influence of solar-driven changes of cloud’s reflective properties and above clouds haze on Jupiter. Because of the orbit eccentricity (e = 0.048450) northern hemisphere obtains on 21 % greater of solar energy flow to the atmosphere, because Jupiter is in perihelia in close to the time of the summer solstice. Results of our studies showed that the ratio of the brightness of the northern and southern tropical and temperate regions Aj is evident factor of the photometric activity of the Jupiter’s atmospheric processes. The obtained from the analysis of observational data for the period from 1962 to 2015, the existence of variations of factor activity Aj of the planet hemispheres with a period of 11.86 years, have allowed us to talk about the existence of the seasonal reconstruction of Jupiter’s atmosphere.